Chiral diboranes as catalysts for the stereoselective organopolymerization of epoxides. Issue 36 (7th September 2022) - Sirin-Sariaslan, Ayla; Naumann, Stefan
Abstract : Chiral diborane catalysts deliver well-defined isotactic-enriched polyether, whereby also polyester-type macroinitiators can be employed. Abstract : It is demonstrated that stereoselective polymerization of epoxides, long a domain of metal-based compounds, can also be achieved via the application of organocatalysts. A simple two-step synthesis starting from widely available 1, 1′-bi-2-naphthol (BINOL) backbones yields diboranes which, in tandem with organobases, deliver isotactic-enriched ( it ) polyethers from the homopolymerization of racemic propylene oxide (PO) and other epoxides. Thereby, isotactic diad contents of up to 88% can be achieved, resulting in well-defined (1.1 < Đ M < 1.3) polyethers with high molar masses ( M n > 100 000 g mol −1 ). Notably, it is also possible to grow it -enriched sequences of PPO on aliphatic polyester-type initiators, thus enabling the incorporation of stereocontrolled polyether blocks in more complex polymer architectures. It is expected that this ability will greatly benefit the preparation of polyether-containing additives. The BINOL-type diboranes can be readily modified, suggesting further potential as a platform from which optimized catalysts can be developed.